Intergranular corrosion in evolving media: Experiment and modeling by cellular automata. (15th August 2022) - Guiso, S.; Brijou-Mokrani, N.; de Lamare, J.; Di Caprio, D.; Gwinner, B.; Lorentz, V.; Miserque, F.
Abstract: We investigate the impact of the oxidizing character of the nitric medium on the evolution of the intergranular corrosion of a stainless steel. In two different oxidizing conditions ("severe" and "soft"), the corroded surface of the steel reaches a different steady state: the oxide is thicker, the intergranular grooves are thinner and the surface area is larger in the "severe" conditions than in the "soft" ones. Then we investigate the effect of an alternative "severe then soft" corrosion sequence. We show that the system re-adapts to the "soft" conditions without memory effect from the previous "severe" ones. Graphical Abstract: ga1 Highlights: The oxidizing power of the nitric acid medium influences the characteristics of the IGC of stainless steels. The more oxidant the nitric acid medium, the thicker the oxide layer. The more oxidant the nitric acid medium, the thinner the groove angles of IGC and the larger the corroded surface. The system re-adapted after a transient time to the new conditions without memory effect from the previous ones. The transient time corresponds to the duration necessary to corrode the equivalent of a layer of grains.